2013
DOI: 10.2337/dc12-0783
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Physical Activity and Risk of All-Cause Mortality and Cardiovascular Disease in Patients With Diabetes

Abstract: OBJECTIVEThe association between habitual physical activity (PA) and lowered risk of all-cause mortality (ACM) and cardiovascular disease (CVD) has been suggested in patients with diabetes. This meta-analysis summarizes the risk reduction in relation to PA, focusing on clarifying dose-response associations.RESEARCH DESIGN AND METHODSElectronic literature searches were conducted for cohort studies that examined relative risk (RR) of ACM or CVD in relation to PA in patients with diabetes. For the qualitative ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
128
2
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(150 citation statements)
references
References 38 publications
12
128
2
8
Order By: Relevance
“…Despite a lack of evidence from randomized studies for the effect of SMB on long-term outcomes, there is some weak indication that specific dimensions of SMB are associated with prolonged life expectancy among diabetes patients. A recent meta-analysis (32) showed that 1-MET/h/day incrementally higher physical activity was associated with a 9.5% reduction in allcause mortality. Based on data from the multicenter ROSSO (Retrolective Study Self-Monitoring of Blood Glucose and Outcome) study, Martin et al (20) reported in their debatable study that SMBG reduces the mortality risk by 50% (33); however, in contrast no effect on all-cause mortality was found in the observational prospective Fremantle Diabetes Study (21).…”
Section: Discussionmentioning
confidence: 99%
“…Despite a lack of evidence from randomized studies for the effect of SMB on long-term outcomes, there is some weak indication that specific dimensions of SMB are associated with prolonged life expectancy among diabetes patients. A recent meta-analysis (32) showed that 1-MET/h/day incrementally higher physical activity was associated with a 9.5% reduction in allcause mortality. Based on data from the multicenter ROSSO (Retrolective Study Self-Monitoring of Blood Glucose and Outcome) study, Martin et al (20) reported in their debatable study that SMBG reduces the mortality risk by 50% (33); however, in contrast no effect on all-cause mortality was found in the observational prospective Fremantle Diabetes Study (21).…”
Section: Discussionmentioning
confidence: 99%
“…Heart disease and stroke account for approximately 65% of deaths among people with diabetes, and individuals classified as prediabetic are also at increased risk for CVD (34). Recent meta-analyses of diabetic cohorts report risk reductions of 29% for CVD incidence (48) and 37% for CVD mortality (49) for those in the highest versus lowest PA category. Walking 2 to 4.5 hours/week is associated with a 46% reduction in CVD mortality compared with walking less than 2 hours/week (49).…”
Section: Physical Activity and Reduced Cardio Vascular Risk: Biologimentioning
confidence: 99%
“…In addition to standard insulin therapy, regular exercise has been suggested to lead to positive effects in patients with diabetes by lowering the risk of cardiovascular diseases and early all-cause mortality (1). Furthermore, it was recently shown that adopting a healthy lifestyle in patients with type 1 diabetes mellitus led to an improvement in body fat, body mass index (BMI) and lipid profiles as well as in blood pressure (2).…”
Section: Introductionmentioning
confidence: 99%